Frequency of Post Endoscopic Retrograde Cholangiopacreatography Pancreatitis in Patients with Pancreatic Disease - Ahmad, Maqsood; Farooq, Shafaq; Kumar, Akash; Raza, Muhammad Adil; Muhammad, Khair; Asma, Asma; Ul-Haq, Moeen- (Journal of Neonatal Surgery, 2025)
Endoscopic retrograde cholangiopancreatography (ERCP) is a technique that combines the use of endoscopy and fluoroscopy to diagnose and treat certain problems of the biliary or pancreatic ductal systems. Post-ERCP pancreatitis (PEP) is diagnosed when patients develop signs and symptoms of acute pancreatitis in addition to elevation of pancreatic enzymes. Objective: To determine the frequency of post ERCP in patients undergoing endoscopic retrograde cholangiopancreatography for pancreatic disease Methodology: This descriptive case series study was conducted at the Gastroenterology Unit of Lahore General Hospital, Lahore, over a duration of six months following the approval of the synopsis, from May 2023 to June 2024. Patients were prepared for the procedure by overnight fasting and received antibiotic prophylaxis with an injection of Ceftriaxone 1 gram. The ERCP procedure was performed under regional anesthesia by a single senior gastroenterologist with a minimum of four years of residency experience. Post-ERCP outcomes were carefully documented. All collected data were entered and analyzed using SPSS version 20. Results: The mean age of patients was 37.19±10.54 years. Abdominal pain was observed in 44(14.33%) patients and PEP was found in 44(14.33%) patients. Conclusion: The frequency of PEP was 14.33% in patients with pancreatic disease